2020
DOI: 10.3390/ma13163516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Temperature on the Compressive Strength and Durability Properties of Crumb Rubber Engineered Cementitious Composite

Abstract: This paper reports the findings of the effect of elevated temperature on the compressive strength and durability properties of crumb rubber engineered cementitious composite (CR-ECC). The CR-ECC has been tested for its compressive strength and chemical resistance test against acid and sulphate attack. Different proportions of crumb rubber (CR) in partial replacement to the fine aggregate and polyvinyl alcohol (PVA) fiber have been utilized from 0 to 5% and 0 to 2%. The experiments were designed based on a cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…As shown in Table 2 , the mixes had varying combinations and levels of the input factors and five randomized duplications for each variable. The duplicate mixes were to ensure the effectiveness of the experiment and guard against possible deviations [ 24 ]. The RSM measures the influence of the interaction between the input factors on the responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 2 , the mixes had varying combinations and levels of the input factors and five randomized duplications for each variable. The duplicate mixes were to ensure the effectiveness of the experiment and guard against possible deviations [ 24 ]. The RSM measures the influence of the interaction between the input factors on the responses.…”
Section: Methodsmentioning
confidence: 99%
“…The optimization is done by assigning targets for the input factors and the responses and level of significance to attain balanced objective functions. The optimization is measured using the “desirability value,” which is measured on a scale of 0 to 1 (0 ≤ d ≤ 1) [ 24 ].…”
Section: Multi-objective Optimization (Mo)mentioning
confidence: 99%
“…The ettringite leads to further expansion and spalling of the concrete. (Mohammed et al, 2020) reported that the presence of CR in the ECC reduced the permeability of the composite and hence reducing the ingress of the sulphate leading to lower expansion rate of the sample prims tested.…”
Section: Sulfate Resistencementioning
confidence: 98%
“…In the past few decades, the waste rubber originated from scrap tyres and rubber products had accumulated to an explicitly large amount, until this issue started threatening the environment [9][10][11]. Approximately 1000 million (M) tyres reach their useful life each year.…”
Section: Introductionmentioning
confidence: 99%